Development of High-Pressure Multigrain X-Ray Diffraction for Exploring the Earth's Interior. (June 2019) - Zhang, Li; Yuan, Hongsheng; Meng, Yue; Mao, Ho-Kwang
Abstract: The lower mantle makes up more than a half of our planet's volume. Mineralogical and petrological experiments on realistic bulk compositions under high pressure–temperature ( P – T ) conditions are essential for understanding deep mantle processes. Such high P – T experiments are commonly conducted in a laser-heated diamond anvil cell, producing a multiphase assemblage consisting of 100 nm to submicron crystallite grains. The structures of these lower mantle phases often cannot be preserved upon pressure quenching; thus, in situ characterization is needed. The X-ray diffraction (XRD) pattern of such a multiphase assemblage usually displays a mixture of diffraction spots and rings as a result of the coarse grain size relative to the small X-ray beam size (3–5 μm) available at the synchrotron facilities. Severe peak overlapping from multiple phases renders the powder XRD method inadequate for indexing new phases and minor phases. Consequently, structure determination of new phases in a high P – T multiphase assemblage has been extremely difficult using conventional XRD techniques. Our recent development of multigrain XRD in high-pressure research has enabled the indexation of hundreds of individual crystallite grains simultaneously through the determination of crystallographic orientations for these individual grains. Once indexation is achieved, each grain can be treated as a single crystal. The combined crystallographic information from individual grains can be used to determine the crystal structures of new phases and minor phases simultaneously in a multiphase system. With this new development, we have opened up a new area of crystallography under the high P – T conditions of the deep lower mantle. This paper explains key challenges in studying multiphase systems and demonstrates the unique capabilities of high-pressure multigrain XRD through successful examples of its applications.